An effective aid programme for Australia : making a real difference - delivering real results (Commonwealth of Australia, 2011)
The Independent Review identified ways to make Australia's aid program more transparent, more accountable, more focussed on results and on real, measurable value for money. It also analysed the overall purpose of Australia's aid program and made recommendations on the appropriate geographic and sectoral focus of Australian aid, and the importance of effective partnerships in delivering Australian aid on the ground.
Keywords: AID PROGRAMMES